1984
DOI: 10.7164/antibiotics.37.1204
|View full text |Cite
|
Sign up to set email alerts
|

Structure and conformation of epimers derived from the antibiotic teicoplanin.

Abstract: Basic hydrolyses carried out on the glycopeptide antibiotic teicoplanin or its acidic hydrolysis products give rise to epimeric species which retain little antibiotic activity. The detailed structure of a sample epimer has been determined using 'H NMR spectroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0
3

Year Published

1987
1987
2003
2003

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 4 publications
1
22
0
3
Order By: Relevance
“…The consequence of this change was the removal of the hydrogen bonding opportunity for this amide hydrogen and the total loss of antibiotic activity. [322] Recent studies demonstrated the feasibility of rupturing certain amide bonds selectively and of excising certain amino acids from the glycopeptide backbone and replacing them with new, even unnatural ones. Hydrolysis of the AA-6/AA-7 amide bond of vancomycin and teicoplanin can be carried out under acidic conditions.…”
Section: Semisynthetic Glycopeptide Antibioticsmentioning
confidence: 99%
“…The consequence of this change was the removal of the hydrogen bonding opportunity for this amide hydrogen and the total loss of antibiotic activity. [322] Recent studies demonstrated the feasibility of rupturing certain amide bonds selectively and of excising certain amino acids from the glycopeptide backbone and replacing them with new, even unnatural ones. Hydrolysis of the AA-6/AA-7 amide bond of vancomycin and teicoplanin can be carried out under acidic conditions.…”
Section: Semisynthetic Glycopeptide Antibioticsmentioning
confidence: 99%
“…In the initiation of binding, the positively charged amino group of amino acid 1 plays an important role in the electrostatic approach of the negatively charged carboxylate anion of the target peptide. 76 The number and position of the chlorine atoms is also critical to the intrinsic activity of dalbaheptides. Most changes near the binding site affect the binding properties and often result in a reduction of antibacterial activity (Table XIX).…”
Section: Alterations Of the Binding Pocketmentioning
confidence: 99%
“…N-15-CBz TD Methyl Ester (8) Starting from 211} and using substantially the same esterification procedure described for 311} 35 g of pure title compoundwere obtained.…”
mentioning
confidence: 99%